‫أﺛﺮ‬‫اﻟﻴﻘﻈﺔ‬ ‫اﻹﺳﱰاﺗﻴﺠﻴﺔ‬ ‫ﰲ‬ ‫اﻟﺘﻨﺒﺆ‬ ‫واﻟﻮﻗﺎﻳﺔ‬ ‫ﻣﻦ‬ ‫اﻷزﻣﺎت‬ ‫ﰲ‬ ‫اﳌﺆﺳﺴﺔ‬ ‫اﻟﻮﻃﻨﻴﺔ‬ ‫ﻟﻺﺗﺼﺎﻻت‬‫"‬ ‫ﻣﻮﺑﻴﻠﻴﺲ‬ ‫"‬‫وﻛﺎﻟﺔ‬ ‫ﺳﻮق‬ ‫أﻫﺮاس‬ - ﺳﻠﻴﻢ ‫ﺳﻠﻄﺎﱐ ‬‬‫; ‬‫ﷴ‬ ‫ﻋﺒﺪ‬ ‫اﻟﺮﺣﻴﻢ‫ﻟﻌﻨﱰي ‬ (My University, 2018)
In this study, we discussed the positive impact of strategic vigilance in the prevention and forecasting of crises in the telecommunications services institution, the study also provided a theoretical briefing on the practice of strategic alertness and crisis management, the field side was used as a main tool for collecting data from the personnel working in the agency, depending on the following problem : What is the impact of the exercise of strategic vigilance in the prediction and prevention of crises in the Mobilis Foundation ? At the end of the research, we have established the relationship between strategic vigilance and crisis management.